Agroecologias: um estudo dos programas de pós-graduação em Agroecologia no Brasil - Sobral, Vivianne Caroline Santos (2019)
This paper presents Agroecology as a scientific area in a consolidation phase in Brazil. In order to demonstrate this, an exploratory research is initially conducted on the emergence of agroecology and its scientific and epistemological basis, as well as its introduction in graduate programs in Brazil. To understand how agroecology constitutes a scientific field, Bourdiesian theory about science along with Kuhn's studies on the scientific paradigm are rescued to reflect on the inclusion of agroecology in the scientific field – which is already dominated by the scientific paradigm of the agrarian sciences. An empirical research is also produced on accredited graduate programs on agroecology on the CAPES portal. Thus, a characterization of the graduate schools is initially made based on the institutional narratives displayed on the webpages of each graduate program/university, and it also includes data on the faculty and the curriculum structure of each agroecology graduate program. The aim is to evaluate if there is coherence between the discourse of each institution, the curricular structure of the courses, and the scientific proposal of agroecology. As a methodological approach, a case study on the graduate studies in Agroecology and Rural Development of the Federal University of São Carlos and some accredited professors in this graduate program are interviewed. These interviews have enriched the analysis of the agroecological scientific area. In addition, some considerations on scientific production (theses and dissertations) in agroecology are carried out together with reflections on how the political scenario can affect the development of the agroecological scientific field. The results point to the growth and consolidation of the agroecological scientific department and some institutional and political obstacles that may hinder the growth of this area of knowledge are listed.